2017
DOI: 10.1249/mss.0000000000001261
|View full text |Cite|
|
Sign up to set email alerts
|

Short-Term Exercise Training Alters Leukocyte Chemokine Receptors in Obese Adults

Abstract: Exercise, in the absence of weight/fat loss and without changes in circulating chemokines, has direct effects on leukocytes in obese adults with HIIT and MICT resulting in different responses. MICT may reduce monocyte migration potential through downregulation of CCR2 and CXCR2, whereas HIIT may increase potential for CCR5-mediated monocyte, neutrophil, and T-cell infiltration. The impact of different exercise protocols on leukocyte trafficking to tissues in obesity warrants further research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
54
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 38 publications
4
54
0
Order By: Relevance
“…Interestingly, we observed a significant decrease in the proportion of CCR2‐expressing HSPCs specifically in individuals with obesity and a decrease in overall CCR2 expression, which was independent of weight status. Our research extends recent research that has shown that exercise can reduce the level of expression of CCR2 on inflammatory monocytes in individuals with obesity (Barry et al . 2017) to show that CCR2 is also reduced in HSPCs, inflammatory monocyte precursors.…”
Section: Discussionsupporting
confidence: 88%
“…Interestingly, we observed a significant decrease in the proportion of CCR2‐expressing HSPCs specifically in individuals with obesity and a decrease in overall CCR2 expression, which was independent of weight status. Our research extends recent research that has shown that exercise can reduce the level of expression of CCR2 on inflammatory monocytes in individuals with obesity (Barry et al . 2017) to show that CCR2 is also reduced in HSPCs, inflammatory monocyte precursors.…”
Section: Discussionsupporting
confidence: 88%
“…This newly proposed short-term intervention indicated an overall unchanged effect on body composition parameters, which was in line with other exercise interventions [19,17,[28][29][30]. However, Robinson et al [15] reported a significant reduction in body weight and BMI following 2 short-term exercise programs (highintensity aerobic training, 4 × 1 min cycling exercise, and moderate-intensity exercise, 50 min of continuous cycling exercises) in the OW/OB prediabetic patients.…”
Section: Discussionsupporting
confidence: 69%
“…In this study, a slight but significant increase was observed in FFM (2.06%) and SMM (1.9%). The combined interventions were effective in increasing muscle mass, while there existed no report on high-intensity aerobic training [28,29]. The incidence of cardiovascular disease (CVD) and its associated total mortality rate could be predicted by evaluating body composition [31], while both the increase in FM and FFM reduction could generate identical %FM values in different conditions from obesity to hidden cachexia; consequently, the effective changes in body composition could not be reflected by %FM alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evaluated the effect of HIIT in obese women with type 2 diabetes and found an improvement in inflammatory profile through the decreased expression of TLR‐4 and TLR‐2 in the cell surface of lymphocytes and monocytes after 2 weeks of training. Furthermore, HIIT induces immune stimulatory actions such as the increasing potential for CCR5‐mediated chemotaxis and improvements in oxidative burst and phagocytosis of stimulated‐leukocytes …”
Section: Discussionmentioning
confidence: 99%